The Usage of Ocular Trauma Scoring in the Visual Prognostic Evaluation of Traumatic Eye Injury - Turgut, Burak; Kobat, Sabiha Güngör; Tanyıldızı, Rumeysa (My University, 2014)
Aim of this study was to investigate the visual prognostic value of ocular trauma score (OTS) in traumatic eye injuries. A hundred and fourteen patients with the ocular trauma, which were underwent surgery between January 2008 and January 2012 at Firat University Hospital Clinic of Ophthalmology, were included in the study. The medical records of the patients were reviewed retrospectively. Similarly to the OTS study group, patients were divided into five groups based on their visual acuity (no light perception (NLP), light perception / hand movements (LP/HM), 1/200-19/200, 20/200-20/50, 20/40 and up) at the presentation. Ocular trauma classification was made according to the Birmingham Eye Trauma Terminology (BETT). The variables used in ocular trauma score (initial and final visual acuity, rupture, endophthalmitis, perforation, retinal detachment, afferent pupillary defect) were evaluated for each patient individually. A numerical value (raw number) was assigned to each of these variables. Numerical values related to the OTS variables were converted into OTS categories and the possible or expected visual outcome and prognosis were obtained. The percentages of the eyes in each category in the OTS study were compared with those of the eyes in our study. The average follow–up duration of patients was 10 months (range 5-12 months). The average age of patients was 24,7± 21,3 years. Of the 27 (24%) were females and 87 (76%) were males. When we compared the table of distribution of final visual acuities in all OTS categories, in our group, NLP ratios were significantly lower in category 1 and 2 (p=0.0017, p=0.00009, respectively), whereas LP/HM ratios in categories 1, 2 and 3were significantly higher in our group than in the OTS study (p=0.00002, p=0.001, p=0.000001, respectively). When we compared final visual acuities in each categories of our study and the OTS study, in our study, 20/200 to 20/50 and 20/40 and over ratios in categories 2 and 3 were significantly lower than those in the OTS study, (p=0.00003, p=0.003, p=0.000001, respectively). 20/200 to 20/50 ratio in category 4 in our group was significantly higher than that in the OTS group (p=0.000001), whereas 20/40 and over ratio in category 4 in our study group was significantly lower than that in the OTS group, (p=0.000001, respectively). Ocular trauma scoring might provide information about visual outcomes of injury and categorical evaluation of traumatic ocular injuries at initial examination
Keywords: Göz Hastalıkları